Picnic in Provence : a memoir with recipes - Bard, Elizabeth (Journalist) (Little, Brown and Company, 2015)
The author describes how she and her husband moved from cosmopolitan Paris to rural Provence after their son was born, the beginning of their adventures as culinary entrepreneurs, and their initiation into classic Proven©ʹal cuisine.